Doping of tantalum, niobium, and hafnium in a translucent ZrO2-SiO2 nanocrystalline glass-ceramic. Issue 4 (April 2022) - Fu, Le; Jiang, Fuqing; Li, Bo; Cheng, Yongxin; Xu, Guofu; Huang, Jiwu; Engqvist, Håkan; Xia, Wei
Highlights: The ternary dopants enhanced the transformability of tetragonal ZrO2 . Lamella nanotwins were formed within many ZrO2 nanocrystallites. No obvious segregation of dopants was detected at ZrO2 grain boundaries. The dopants imparted a yellowish- or dark-brown color to the glass-ceramics. Tetragonal and monoclinic ZrO2 were metastable in the thermal treatments. Abstract: The addition of dopant(s) is an effective strategy to regulate the microstructure and properties of ZrO2 -based ceramics. In this study, we investigated the effects of ternary element alloying, namely tantalum (Ta), niobium (Nb), and hafnium (Hf) elements, on the microstructure and transformability of ZrO2 nanocrystallites in a ZrO2 -SiO2 nanocrystalline glass-ceramic (NCGC) during sintering and thermal treatments. The ternary dopants enhanced the transformability of tetragonal ZrO2 (t-ZrO2 ) nanocrystallites during sintering, i.e., the dopants acted as t-ZrO2 destabilizer. The Ta, Nb and Hf elements dissolved in ZrO2 nanocrystallites, forming ZrO2 solid solution. Meanwhile, lamella nanotwins were formed within many ZrO2 nanocrystallites. No obvious segregation of dopants was detected at ZrO2 grain boundaries. t-ZrO2 and monoclinic (m) ZrO2 nanocrystallites were metastable in thermal treatments process, with "t" to "m" and the reverse "m" to "t" polymorphic transformation occurred simultaneously. Meanwhile, t-ZrO2 and m-ZrO2 nanocrystallites had a great tendency to grow larger during thermal treatments.